Islam, Wacana Negara dan Geliat Politik di Indonesia - Abdullah A Afifi; Afifi Fauzi Abbas (IDRIS Darulfunun Institute, 2023)
Islam is a religion that contains ethical values that discuss various sectors of society's social life. Meanwhile, the state is a complex social system. The state is a forum that accommodates the participatory activities of all its citizens. The existence of leadership and government in Islam is crucial, given its relevance in maintaining the law to ensure justice and benefit for citizens in this social system. The processes for developing leadership, government, and the state are determined by every citizen with the mechanism of political party representatives. The role of political parties is to connect elements between the non-formal aspirations of citizens to be advanced at a formal level so that they can be encouraged to become policies that provide benefits for all citizens. The dynamics of the transformation of the conception of government and the state continue to develop contextually, following the social structure of the people and the world order globally. This article discusses the conception of the state with descriptive analysis using classical and contemporary literature. This article also elaborates on how political activity in Indonesia needs to achieve a mature state so that the political activities of Islamic parties can provide practical and in-depth solutions to the problems of citizens as a whole.